The old and the death. - Vianna, Lucy Gomes; Loureiro, Altair; Alves, Vicente Paulo; Vianna, Cecília (Revista Kairós-Gerontologia, 2014)
The fear of death comes from the fear of physical destruction of the body, which, in contemporary society is narcissistically valued. Adopting the youth as its main model, this society stigmatizes the old. This situation arouses different ways of coping, ranging from one being to another. We discuss the forms of understanding the old age and the death in elderly subjects living in the community and institutionalized.